Analisis Kepemimpinan Transformasional dalam Meningkatkan Motivasi dan Kinerja Pegawai: Perspektif Islam, Studi Kantor PPK O&P Sda IV Bojonegoro - Lantip Lantip (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the contribution of transformational leadership in enhancing employee motivation and performance at the Work Unit Office of PPK O&P SDA IV Bojonegoro from an Islamic perspective. In the context of government organizations, the role of leaders is crucial in shaping employee performance and achieving organizational goals. Transformational leadership is known for its ability to inspire, motivate, and stimulate employees to exceed predetermined targets. The Islamic perspective emphasizes that good leadership is based on values of justice, honesty, and responsibility. This research employs a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with employees and leaders at the Work Unit Office of PPK O&P SDA IV Bojonegoro, as well as direct observation of organizational dynamics. The collected data were analyzed using thematic analysis to examine the relationship between transformational leadership style and the level of employee motivation and performance. The findings indicate that the implementation of transformational leadership at the Work Unit Office of PPK O&P SDA IV Bojonegoro enhances employee motivation through individual empowerment, the establishment of a clear vision, and the provision of inspiration that drives the achievement of shared goals. High motivation leads to improved employee performance, making them more productive and creative in completing their tasks. In conclusion, the application of transformational leadership from an Islamic perspective significantly enhances employee motivation and performance..  Keywords: Leadership, Transformational, Motivation, Islam